2017
DOI: 10.1007/s00382-017-3849-9
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence of deep convection in the Arctic Ocean under a warming climate

Abstract: The appearance of winter deep mixed layers in the Arctic Ocean under a warming climate is investigated with the HiGEM coupled global climate model. In response to a four times increase of atmospheric CO2 levels with respect to present day conditions, the Arctic Basin becomes seasonally ice-free. Its surface becomes consequently warmer and, on average, slightly fresher. Locally, changes in surface salinity can be far larger (up to 4 psu) than the basin-scale average, and of a different sign. The Canadian Basin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Although its contribution to the changes of the liquid FWC is relatively small compared to the larger changes of the Barents Sea branch AW and the Pacific Water, the Fram Strait inflow can also impact the deep AW layer circulation. Previous studies have indicated that weaker sea ice and changes in ocean surface circulation can influence the AW layer circulation located at depth (Karcher et al 2012;Itkin et al 2014;Lique et al 2015). In this paper we focus on the Arctic surface freshwater, while the model results indicate that dedicated future work is needed to better understand the processes that can influence the fate of the AW in the Arctic Ocean in a changing climate, in particular, in terms of possible changes in the AW layer circulation.…”
Section: A Impact Of Sea Ice Declinementioning
confidence: 94%
See 2 more Smart Citations
“…Although its contribution to the changes of the liquid FWC is relatively small compared to the larger changes of the Barents Sea branch AW and the Pacific Water, the Fram Strait inflow can also impact the deep AW layer circulation. Previous studies have indicated that weaker sea ice and changes in ocean surface circulation can influence the AW layer circulation located at depth (Karcher et al 2012;Itkin et al 2014;Lique et al 2015). In this paper we focus on the Arctic surface freshwater, while the model results indicate that dedicated future work is needed to better understand the processes that can influence the fate of the AW in the Arctic Ocean in a changing climate, in particular, in terms of possible changes in the AW layer circulation.…”
Section: A Impact Of Sea Ice Declinementioning
confidence: 94%
“…By using a coupled climate model Lique et al (2018) showed that the Amerasian basin will become fresher while the Eurasian basin will become more saline due to sea ice decline in future warmer climate (in a 4 3 CO 2 scenario). Our study indicates that the sea ice decline in the past decade has already started this changing tendency.…”
Section: A Impact Of Sea Ice Declinementioning
confidence: 99%
See 1 more Smart Citation
“…HiGEM is a fully coupled climate model based on the Hadley Centre Global Environmental Model version 1 (HadGEM1; Johns et al, 2006) with a relatively high resolution ocean and a reasonable representation of the Arctic (Lique et al, 2015(Lique et al, , 2017. HiGEM is a fully coupled climate model based on the Hadley Centre Global Environmental Model version 1 (HadGEM1; Johns et al, 2006) with a relatively high resolution ocean and a reasonable representation of the Arctic (Lique et al, 2015(Lique et al, , 2017.…”
Section: Model Details and Methodologymentioning
confidence: 99%
“…We analyze monthly mean output from a 150-year control integration performed with the High-Resolution Global Environmental Model (HiGEM). HiGEM is a fully coupled climate model based on the Hadley Centre Global Environmental Model version 1 (HadGEM1; Johns et al, 2006) with a relatively high resolution ocean and a reasonable representation of the Arctic (Lique et al, 2015(Lique et al, , 2017. The model is described and evaluated in Shaffrey et al (2009).…”
Section: Model Details and Methodologymentioning
confidence: 99%